Untangling the puzzle of "Russia's influence" in Kazakhstan. Issue 2 (4th March 2019) - Laruelle, Marlene; Royce, Dylan; Beyssembayev, Serik
ABSTRACT: The theme of "Russian influence" has been invading the think tank world. Yet the concept of influence must be deployed with care. Analysts have frequently assumed that, when states do things thought favourable to Russia, it must be because Moscow has either forced them to act in that manner, or has actively manipulated their domestic politics so that they do so. Left largely unconsidered are the various other reasons that one state might act in a manner desirable to another. In this article we look at the different vectors that might yield Russia-favorable behavior by Kazakhstan: exogenous ones that Russia actively and passively generates and endogenous ones that are passively or even actively generated within Kazakhstan itself. We discuss Russia's economic and strategic links with Kazakhstan, the issue of the Russian minority, the status of the Russian language, Russian media presence, Russia's governmental and non-governmental networks, and the "payoff" of the latter three vectors: Kazakhstani popular Russophilia. By distinguishing between active and passive vectors, as well as between exogenous and endogenous ones, we propose a more nuanced and better theoretically articulated picture of Russia's "influence" in Kazakhstan.